2014
DOI: 10.15193/zntj/2014/96/206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brewing Time and Fragmentation Degree of Black Tea on Colour of Infusion and Its Antioxidant Properties

Abstract: Celem pracy było określenie wpływu czasu parzenia, stopnia rozdrobnienia oraz marki herbaty czarnej na barwę naparu i jego właściwości przeciwutleniające. Oznaczono całkowitą zawartość polifenoli, aktywność przeciwutleniającą oraz parametry barwy L*, a*, b* w systemie CIE Lab w naparach herbat czarnych (liściowych, granulowanych oraz ekspresowych), zakupionych na terenie Trójmiasta i w Anglii. Wykorzystując wyniki analizy głównych składowych podjęto próbę klasyfikacji jakościowej badanych herbat.Stwierdzono, ż… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Results showed that TPC, TFC is positively and highly correlated with fragmentation degree expressed as bulk density (r = 0.73, p < 0.05 and r = 0.79, p < 0.05 respectively). Dmowski et al (2014) did not found any statistical significance between content of total polyphenols and fragmentation degree of infusions of selected black teas regardless of the time of extraction (3 and 15 minutes). In our results, no correlation was observed between TPC and antioxidative activity with DPPH and ABTS radicals in aqueous extracts prepared from dry hawthorn fruits.…”
Section: Figure 2 Malic Acid Oxalic Acid and Tartaric Acid Content mentioning
confidence: 61%
“…Results showed that TPC, TFC is positively and highly correlated with fragmentation degree expressed as bulk density (r = 0.73, p < 0.05 and r = 0.79, p < 0.05 respectively). Dmowski et al (2014) did not found any statistical significance between content of total polyphenols and fragmentation degree of infusions of selected black teas regardless of the time of extraction (3 and 15 minutes). In our results, no correlation was observed between TPC and antioxidative activity with DPPH and ABTS radicals in aqueous extracts prepared from dry hawthorn fruits.…”
Section: Figure 2 Malic Acid Oxalic Acid and Tartaric Acid Content mentioning
confidence: 61%
“…Similar results were reported by Yen and Chem (1995), who found the most antioxidant compounds in 5-minute infusions. Dmowski et al (2014) gived that prolonging the brewing time from 3 to 15 minutes resulted in an increase in antioxidant activity, but only for some types of black teas. Wang et al (2005) found that excessively long brewing time significantly reduces the antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
“…A similar trend was observed in the study on the antioxidant potential of black teas. Dmowski et al (2014) found that an extended brewing time leads to the increased antioxidative activity of tea. Infusions prepared from herbal granules showed significantly lower activity to react with the DPPH radical when compared to teas from the control; on average by 53% in the case of lemon balm, 42% -sage and 14% -chamomile.…”
Section: Resultsmentioning
confidence: 99%
“…The colour parameters of herbal infusions were measured using a Lovibond CAM-System 500 tintometer. Glass measuring containers were filled with 50 cm 3 portions of prepared teas, placed on measuring heads and determined according to CIE Lab scale, where L* stands for lightness, a* stands for redness and greenness and b* yellowness and blueness (Dmowski et al, 2011;2014).…”
Section: Colour Parametersmentioning
confidence: 99%
See 1 more Smart Citation